Analisis Yuridis Penyelesaian Sengketa Perbatasan Laut Antara Indonesia Vietnam Di Perairan Zona Ekonomi Eksklusif Indonesia - Ayu S, Rizza; Ramlan , Ramlan; Repindowaty, Rahayu (Uti Possidetis: Journal of International Law, 2021)
The sea border between Indonesia and Vietnam is a maritime border located in the South China Sea. Until now, there have been several problems that have occurred especially in the exclusive economic zone between Indonesia and Vietnam, which have not been completely resolved. The exclusive economic zone is an area outside and adjacent to the territorial sea which is subject to a special legal regime for international maritime law. Based on the principles of international peace and security, there are several attempts shown to create good relations between countries in resolving disputes that occur. The principle referred to in resolving international disputes is to provide a way for parties to a dispute to resolve their disputes based on international law. There are two methods of settlement known in international law, that is peacefully and in war (military). Dispute settlement procedures for countries that are interconnected with maritime territories between countries can be seen in Article 287 UNCLOS 1982 which regulates alternatives and dispute resolution procedures. This research is a normative study that examines sources related to the issues discussed. The results of this study conclude that in resolving disputes between Indonesia and Vietnam regarding maritime boundaries in the waters of the Exclusive Economic Zone, it can be resolved with various alternative dispute resolution alternatives as described in the 1982 UNCLOS framework, that is a) peaceful dispute resolution, b) dispute resolution with mandatory procedures. Each country is given the freedom to choose an alternative that will be used in resolving the dispute that is being faced what both parties want both take the litigation route (court route)as well as non-litigation channels (out of court) as regulated in Article 280 UNCLOS 1982.